2012
DOI: 10.1097/brs.0b013e31824586a8
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Treatment of Dural Tears and Cerebrospinal Fluid Leakage in 266 Patients With Thoracic Myelopathy Caused by Ossification of the Ligamentum Flavum

Abstract: Dural ossification was the main reason for dural tears. In all, 78 of the 85 patients with CSF leakage or dural tear were successfully cured. The success rate was 91.8%, which indicated that a series of comprehensive treatments was an effective strategy to treat these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 24 publications
1
85
0
Order By: Relevance
“…Our findings are consistent with previous studies that have reported the incidence of dural tears and CSF leaks to be 11% to 32%. 7,11,12,24,25 One potential explanation for the significant rate of dural tears and CSF leaks is the potential technical challenge encountered by the presence of dural ossification, which has been described by several authors. 16,17,19 The pathophysiology of OLF can lead to ossification of the dura mater, resulting in fusion of the ligamentum flavum and dura into a single inseparable layer of bony tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous studies that have reported the incidence of dural tears and CSF leaks to be 11% to 32%. 7,11,12,24,25 One potential explanation for the significant rate of dural tears and CSF leaks is the potential technical challenge encountered by the presence of dural ossification, which has been described by several authors. 16,17,19 The pathophysiology of OLF can lead to ossification of the dura mater, resulting in fusion of the ligamentum flavum and dura into a single inseparable layer of bony tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The intraoperative manipulation should be gentle to avoid dural tears as much as possible, and once a dura mater tear is noticed, immediate repair should be carried out. 56,68,70 Eight cases underwent dura mater repair and no CSF leakage happened after the operation, and the surgical effect was satisfactory. Although the procedure and success of intraoperative repair is important, comprehensive treatments after operation should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Dural tears and CSF leakage are the most common complications of thoracic OLF surgery and can lead to CSF pseudocyst, respiratory obstruction, wound dehiscence and meningitis. [66][67][68] Because dural adhesion and DO are more common in thoracic OLF than in cervical or lumbar spine, the incidence of CSF leakage in OLF patients may be higher. 56,[68][69][70] Miyakoshi et al 56 reported that dural adhesion was observed in 62% of the 34 patients with OLF, and found that dural adhesion was frequently observed in larger types of OLF.…”
Section: Discussionmentioning
confidence: 99%
“…Specialists diagnosed TOLF based on clinical symptoms and radiological examination as previously described [47]. Ligamentum flavum samples were obtained from TOLF patients during spinal surgery via en bloc resection of the lamina and ligamentum flavum as previously described [48]. …”
Section: Methodsmentioning
confidence: 99%